998 Reducing unnecessary iv starts in children with diabetes presenting to the emergency department. (21st November 2017) - Baumer-Mouradian, Shannon; Gray, Matt; Chang, Franklin; Wolfgram, Peter; Brousseau, David; Ferguson, Catherine
Abstract : Background: Unnecessary medical interventions prolong emergency department (ED) stays and increase costs. We found that 83% of children with diabetes mellitus (DM) presenting to the ED not in diabetic ketoacidosis (DKA) underwent unnecessary IV placement. Objectives: We aimed to decrease IV placements to 20% within 18 months for children presenting to the ED with known DM not meeting DKA criteria. Methods: This QI project was conducted in a tertiary care paediatric ED and included children with known DM. Plan-do-study-act cycles included point-of-care (POC) testing, order panel use, and DKA clinical care and nursing guidelines. Outcome measures, analysed on statistical process control charts, included number of IV starts and time to first bicarbonate result. The percent of patients receiving unnecessary IV starts was analysed using the Chi-square test. Process measures included rate of POC testing and order panel utilisation. Results: Between January 2015 and July 2017, 294 DM patients were evaluated for DKA. 168 patients (57%) did not meet DKA criteria. In those patients without DKA, the overall number of unnecessary IV starts decreased from 83% pre-interventions to 41% post-interventions (p<0.001; Fig 1). In the same 168 patients, mean time to first bicarbonate decreased from 78 to 29 min (62%) after implementation of all four interventions (Fig 2). Use of POC testing and order panels increased from zero to 92% and 75%, respectively. Conclusions: Using QI methodology, we achieved a meaningful reduction in unnecessary IV starts and time to DKA determination in patients presenting with known DM found not to have DKA.